Clear cell renal cell carcinoma with focal psammomatous calcifications: a rare occurrence mimicking translocation carcinoma - Sangoi, Ankur R; Al-Obaidy, Khaleel I; Cheng, Liang; Kao, Chia-Sui; Chan, Emily; Sadasivan, Sudha; Levin, Albert M; Alvarado-Cabrero, Isabel; Kunju, Lakshmi P; Mehra, Rohit; Mannan, Rahul; Wang, Xioming; et al. (Histopathology, 2023)
AIMS: Renal cell carcinoma (RCC) with clear cells and psammoma-like calcifications would often raise suspicion for MITF family translocation RCC. However, we have rarely encountered tumours consistent with clear cell RCC that contain focal psammomatous calcifications. METHODS AND RESULTS: We identified clear cell RCCs with psammomatous calcifications from multiple institutions and performed immunohistochemistry and fluorescence and RNA in-situ hybridisation (FISH and RNA ISH). Twenty-one tumours were identified: 12 men, nine women, aged 45-83 years. Tumour size was 2.3-14.0 cm (median = 6.75 cm). Nucleolar grade was 3 (n = 14), 2 (n = 4) or 4 (n = 3). In addition to clear cell pattern, morphology included eosinophilic (n = 12), syncytial giant cell (n = 4), rhabdoid (n = 2), branched glandular (n = 1), early spindle cell (n = 1) and poorly differentiated components (n = 1). Labelling for CA9 was usually 80-100% of the tumour cells (n = 17 of 21), but was sometimes decreased in areas of eosinophilic cells (n = 4). All (19 of 19) were positive for CD10. Most (19 of 20) were positive for AMACR (variable staining = 20-100%). Staining was negative for keratin 7, although four showed rare positive cells (four of 20). Results were negative for cathepsin K (none of 19), melan A (none of 17), HMB45 (none of 17), TFE3 (none of 5), TRIM63 RNA ISH (none of 13), and TFE3 (none of 19) and TFEB rearrangements (none of 12). Seven of 19 (37%) showed chromosome 3p deletion. One (one of 19) showed trisomy 7 and 17 without papillary features. CONCLUSIONS: Psammomatous calcifications in RCC with a clear cell pattern suggests a diagnosis of MITF family translocation RCC; however, psammomatous calcifications can rarely be found in true clear cell RCC.
Keywords: Carcinoma, Renal Cell; TFE3; lidé; TFEB; Calcinosis; karcinom z renálních buněk; Kidney Neoplasms; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Biomarkers, Tumor; psammoma bodies; kalcinóza; ženské pohlaví; nádorové biomarkery; Humans; transkripční faktory BHLH-Zip; Chromosome Aberrations; chromozomální aberace; TRIM63; clear cell renal cell carcinoma; Translocation, Genetic; translokace genetická; Female; nádory ledvin